Pendekatan Baharu Kutipan Zakat di Negeri Kedah - M.F., Osman.; Md Hussian, Muhammad Nasri; Md Yusuf, Syarifah; Long, Muhammad Noor Habibi; Harun, Mohd Sani (Lembaga Zakat Negeri Kedah, 2022)
The reluctance of paying zakat among Muslims became such a big issue during the time of the Caliph Abu Bakar Assiddiq until he declared war on those who refused to pay zakat. Nowadays, there are some Muslims who feel reluctant to pay zakat to the zakat institution. Otherwise, they prefer to pay zakat directly to the asnaf that they have decided on their own. This affects the amount of collection by the zakat institution, thus reducing the amount of distribution to asnaf. As a result, the asnaf could not be fully assisted and various forms of assistance could not be implemented. However, Kedah has seen a significant increase in zakat collection lately. Therefore, this study aims to identify the transformation of the zakat collection implemented in Kedah State. Qualitative research focuses on library research and field research. The results of the study found that LZNK uses information technology as a medium to transform the management of Kedah zakat collection. LZNK develops an information database. The total of daily and monthly collection, as well as yearly collection could be accessed in real time by the public through the LZNK Website. The transformation using this information technology system builds the confidence of zakat payers and further increases the annual collection of zakat in the state of Kedah. The transformation implemented in Kedah should be highlighted so that all zakat institutions can emulate it